SUBMICROSCOPIC CHANGES IN THE SPLEEN OF MATURE RATS UNDER CONDITIONS OF CHRONIC HYPERHOMOCYSTEINEMIA - Grytsenko А.S.; Samborska, I.A.; Lavrinenko, V.Y.; Matkivska R.М. (World of Medicine and Biology, 2024)
In mature rats with hyperhomocysteinemia, pronounced destructive processes in the spleen were observed. A high degree of apoptosis of lymphocytes of the white pulp of the spleen and proliferation of B-lymphocytes into mature plasma cells were noted. The number of lysosomes and phagosomes increased in macrophages, and their cytoplasm contained fragments of destroyed formed blood elements. A significant number of lymphoblasts characterised the active immune response of the organ to hyperhomocysteinemia. The red pulp of the spleen was characterised by increased disintegration of erythrocytes and platelets and accumulation of lipofuscin granules in the cytoplasm of macrophages. Endothelial cells of sinusoidal capillaries were also changed.